Labor Effects of Adult Mortality in Tanzanian Households - Beegle, Kathleen (World Bank, Washington, DC, 2014)
Due to the HIV/AIDS epidemic, sub-Saharan populations are challenged with increasing adult mortality rates that have potentially profound economic implications. Yet, little is known about the impact of adult deaths in African households. Using panel data from Tanzania, this paper will explore how prime-age adult mortality impacts the time allocation of surviving household members and the portfolio of household farming activities. Analysis of farm and chore hours across demographic groups generally found small and insignificant changes in labor supply of individuals in households experiencing a prime-age adult death. While some farm activities are temporarily scaled back and wage employment falls after a male death, households did not shift cultivation towards subsistence food farming and did not appear to have reduced their diversification over income sources more than six months after a death.